A compact hollowed‐out loop rectenna without matching network for wireless sensor applications. Issue 11 (9th September 2020) - Jing, Jianwei; Pang, Jiafei; Wang, Shaoyue; Qiu, Zhenyu; Liu, Changjun
Abstract: In this article, a compact and high‐efficiency loop rectenna with matching network elimination for wireless sensor applications at 2.45 GHz is presented. The proposed hollowed‐out square loop antenna is designed and directly provides a conjugate matching to a compact voltage‐doubler rectifier. The loop rectenna can harvest microwave power without increasing the total size or affecting the performance of a wireless sensor. The experiment results show that the peak microwave‐to‐dc conversion efficiency of 74% is obtained at 2.45 GHz when the input power is 18 dBm. The dimension of rectenna is 30 × 30 × 1 mm 3 and only with a weight of 0.58 g, which successfully realizes a high power‐weight‐ratio (PWR). Hence, the proposed rectenna can provide a convenient and practical charging solution for wireless sensors in various applications.